Effect of Chronic Rhinosinusitis With or Without Nasal Polyp on Quality of Life in South Korea: 5th Korea National Health and Nutrition Examination Survey Korean - Do Hyun Kim; Kyungdo Han; Soo Whan Kim (Clinical and Experimental Otorhinolaryngology, 2016)
Objectives This is the first study of its kind to investigate the relationship between chronic rhinosinusitis (CRS) with or without nasal polyps (NP) and health-related quality of life (HRQoL) in the general adult Korean population. We sought to evaluate the association after adjustment for confounding factors. We also evaluated HRQoL according to presence of NP in CRS patients. Methods In this cross-sectional study we used nationally representative samples from the 5th Korea National Health and Nutrition Examination Survey (2010–2012). A total of 17,490 participants were included in the study, of which 613 were diagnosed with CRS. Univariate analysis was conducted on healthy versus CRS groups, segregated by gender with weighted prevalence of demographic characteristics, socioeconomic status, and comorbid diseases. Subanalysis was carried out to evaluate the relationship between CRS with or without NP and HRQoL using EuroQol 5-dimension (EQ-5D) and visual analog scale (EQ-VAS). The odds ratios for EQ-5D were estimated by multiple logistic regression analyses with confounder adjustment. Results Weighted prevalence of CRS of adult male was found to be 3.7% and CRS with nasal polyps (CRSwNP) 0.5%, while female CRS was 3.3% and CRSwNP 0.3%. There was no significant difference between the groups (P#x0003d;0.332). The scores for female, EQ-5D index (P for trend<0.001) and EQ-VAS (P for trend=0.002) showed decreasing trend from healthy participants to CRS without nasal polyps (CRSsNP) and from CRSsNp to CRSwNP. After adjusting for demographic characteristics, socioeconomic status, and comorbid diseases, EQ-5D scores; EQ-5D index (P<0.001) and EQ-VAS (P<0.001) exhibited poorer HRQoL compared to healthy participants, exclusively within the female group. Conclusion These data suggest that female patients with CRS are at higher risk of poor HRQoL. In addition, HRQoL of female CRSwNP was lower compared to those of CRSsNP and healthy participants.